Evaluasi Kepatuhan Pelaksanaan Program Vaksinasi Covid-19 I - IGAA Sherlyna Prihandhani; Made Oktaviani Bulan Trisna (Jurnal Keperawatan Malang, 2023)
The implementation of the COVID-19 vaccination program is expected to gradually reach all target targets. To strengthen the prevention program through vaccination, 5M health protocols also need to be implemented to minimize the spread of COVID-19. The success of the Covid-19 vaccination program will be measured by identifying which parties are working with the government to foster cooperation, and this will provide an overview of how the policy or program is implemented. his research is qualitative. This study aims to evaluate the implementation of the primary and booster vaccination programs is important to prevent non-compliance with vaccination patients to minimize the transmission of COVID-19. This program is carried out for a week by giving interviews to vaccination program holders at UPTD Puskesmas. Data will be analyzed univariately in the elaboration Evaluation of the implementation of the primary and booster vaccination programs in terms of patient compliance at the Mengwi I Health Center. The output of this study shows that the achievement indicator of success in winning the primary reaches 100%, but for the implementation of booster activation, the indicator of success only reaches 70%. The implementation of primary vaccination is carried out more evenly when compared to the implementation of booster vaccinations. Thus, It is hoped that the administration of vaccines can be carried out evenly so that a healthy community is created and the whole community receives vaccinations